Improvement on microstructure of concrete by polycarboxylate superplasticizer (PCE) and its influence on durability of concrete. (1st May 2016) - Huang, Haoliang; Qian, Chunxiang; Zhao, Fei; Qu, Jun; Guo, Jingqiang; Danzinger, Michael
Highlights: Influence of PCEs on carbonation, permeability and chloride penetration in concrete was studied. Pore structures of mortars with different PCEs were explored by means of MIP. Components in cement paste with different PCEs were analyzed by means of TG/DSC. Ratio of HD C–S–H to LD C–S–H affected by PCEs was quantified by nano-indentation. Abstract: In this study, the influence of polycarboxylate superplasticizers (PCEs) on durability of concrete was investigated. Carbonation, water impermeability and rapid chloride permeability of concrete with different types of polycarboxylate superplasticizer and polynaphthalene superplasticizer (PNS) were tested. In order to obtain deeper insights into the influence of PCE on concrete durability, microstructure in the concrete was explored by means of mercury intrusion porosimetry (MIP), thermogravimetry (TG) and nano-indentation technique. Smaller carbonation depth, water penetration depth and better resistance to chloride ion penetration show that concretes with PCE have better durability performances than concretes with PNS. MIP results show that the mortars with PCE have lower porosity than that with PNS. The fraction of pores with diameters larger than 100 nm in the mortars with PCE is lower than in the mortar with PNS. According to TG tests, there are more hydration products in the cement pastes with PCE than in the cement pastes with PNS. Nano-indentation tests show a higher ratio of high density C–S–H to low density C–S–H in the cement paste with PCE than in the cement paste with PNS. It can be concluded that PCE leads to denser microstructure in concrete than PNS and, therefore, better durability performances of concrete.